Analisis Pendidikan Multikultural pada Siswa Sekolah Dasar melalui Keragaman Budaya - Mae Afriliani; Magdalena Magdalena; Siti Fadia Nurul Fitri; Tin Rustini (Departement of Mathematics Education, 2024)
Indonesian is made up of a varietyof nationalities, RACES, languages, customs, cultyres, religions and classes. National education systemz should therefore also accommodate the diversity and diversity of the culture. A multicultural education is applied to student can provide understanding and thus be able to accept differences, crititicisme, and have empathy and tolerance. The study aims to know how the implementation of multicultural education in elementary school in cultural diversity does not remove one another’s distinctive characteristics, adding that Indonesian diversity becomes even richer. The study used library reserch, that is a series of studies relating to library data collection methods, or research that the object of his research was unearthed through various literature information (books, encyclopedisa, scientific jurnals, newspaper magazine, and documents) Arikunto, 2014). With the implementation of multicultural education in elementary schools, it is expected that students can develop awareness and maturity in the face of.